Design of stable liquid infused surfaces: Influence of oil viscosity on stability - Sasidharanpillai, Arun; Lee, Younki; Lee, Seunghyup (Colloids and surfaces. A, Physicochemical and engineering aspects, 2022)
Slippery liquid-infused porous surfaces (SLIPS) have been used as a good alternative for superhydrophobic coatings due to their increased durability against mechanical forces and their ability to repel liquids with a wide range of surface tensions. SLIPS generally consists of a superhydrophobic porous structure infiltrated with a lubricant. The self-healing ability of SLIPS helps to maintain their water repellency longer than superhydrophobic surfaces. Even though SLIPS have great functionalities for practical applications, their stability is still insufficient due to the loss of lubricant from them. The oil loss from SLIPS depends mainly on the viscosity of the lubricant infiltrated into it. Even though plenty of research has been conducted over SLIPS with viscosities ranging from 1 cSt to 20, 000 cSt, a complete understanding of the oil loss mechanism is still not available. Therefore, in this work, we investigated the influence of silicone oil (lubricant) viscosity on the stability of SLIPS to determine a suitable viscosity range to fabricate stable SLIPS. Various SLIPS were fabricated by infiltrating silicone oils with a wide viscosity range. Stability studies were conducted by obtaining the volume of oil removed from the SLIPS with respect to the number of drops. Narrow SLIPS were also fabricated to understand the effect of self-healing speed on the oil loss process. Finally, a dynamic wicking experiment is conducted to determine the self-healing speed of silicone oils. SLIPS with silicone oil viscosities of 3000 cSt and 5000 cSt demonstrated lower loss rates and higher stability. However, the oil loss was fastest for SLIPS with 100 cSt silicone oil. Rapid self-healing of the lower viscosity oil was the main reason for the quick oil loss from lower viscosity SLIPS. [Display omitted] •Stability of liquid infused surfaces were investigated as a function of viscosity of the infiltrated lubricant.•The magnitude of the self-healing speed determines the lubricant loss from SLIPS.•Lower viscosity SLIPS have lower stability due to the higher self-healing speed.•Stable SLIPS were fabricated by infiltrating with higher viscosity lubricants.